Ingestion of Exopolymers from Aureobasidium pullulans Reduces the Duration of Cold and Flu Symptoms: A Randomized, Placebo-Controlled Intervention Study - Choi, Jae-Suk; Baek, Kyung Min; Lee, Seo-Young; Cho, Hyung-Rae; Jung, Go-Woon; Park, Dong-Chan; Do, Eunju; Lim, Jong Min; Shin, Jae Wook (Evidence-based complementary and alternative medicine, 2018)
Aim. The objective of the study was to assess the efficacy of exopolymers from Aureobasidium pullulans (EAP) on the incidence of colds and flu in healthy adults. Methods. We conducted a randomized, double-blind, placebo-controlled study at the onset of the influenza season. A total of 76 subjects (30–70 years of age) were recruited from the general population. The subjects were instructed to take one capsule per day of either EAP or a placebo for a period of 8 weeks. The duration of cold and flu symptoms, a primary variable in assessing effectiveness, and serum cytokine levels as well as WBC counts as secondary variables were also evaluated. Results. EAP was associated with a statistically significant decrease in the duration of cold and flu symptoms, a primary variable in assessing effectiveness. Although cold and flu symptom levels were not significantly different at a significance level of 5%, the cold and flu symptom levels of the EAP group were less severe compared to the placebo group. No statistically significant changes of serum cytokine levels as well as WBC counts were observed. Conclusion. The results showed that EAP is a useful pharmaceutical and functional food material for preventing and treating colds and flu.